2013
DOI: 10.1177/0971852413498741
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure of Gender Identity in Internet Forums: A Case Study of Saudi Arabian Forum Communication

Abstract: Internet discussion forums provide opportunities for largely anonymous communication among participants. The extent to which these opportunities are taken up is of particular interest in cultures where gender relations are highly regulated and cross-gender communication is strictly limited, such as in Saudi Arabian society. This article studies participation in a public discussion forum of expatriate Saudi students. It focuses on the nature of information (whether accurate or not) that participants choose to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…But a study by Madini and de Nooy (2013) has found that almost all of the women revealed their gender in the Saudi online communities they studied; either through the choice of their usernames or within the content of their messages. Revealing sensitive information in SNS such as address, city where one lives or school where one studies in addition to indicating gender can make users, especially Saudi women, vulnerable to blackmail.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…But a study by Madini and de Nooy (2013) has found that almost all of the women revealed their gender in the Saudi online communities they studied; either through the choice of their usernames or within the content of their messages. Revealing sensitive information in SNS such as address, city where one lives or school where one studies in addition to indicating gender can make users, especially Saudi women, vulnerable to blackmail.…”
Section: 2mentioning
confidence: 99%
“…This uniqueness makes this study a contribution to the scarce literature on computermediated communication (CMC) in gender-segregated societies such as the Saudi (Madini & de Nooy, 2013). Given the conservative nature of the Saudi society (see below section for more details on this issue) and the sensitivity of the topic it is difficult for a male researcher to recruit let alone interview women who had actually suffered from blackmail.…”
Section: Introductionmentioning
confidence: 99%
“…The forum thus offers the possibility of anonymous communication and of presenting a gender-neutral identity. 4 A separate article (Madini and de Nooy, 2013) details the analysis of the extent to which these possibilities are taken up. Postings to the forum were examined for clues signaling participants' gender.…”
Section: Identification Of Gender Of Participantsmentioning
confidence: 99%